2015
DOI: 10.12783/issn.1544-8053/12/2/11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heavy Metal and Nutrients on Benthic Microbial Communities in Freshwater Sediment of Poyang Lake (China)

Abstract: ABSTRACT:The aim of this work was to relate sediment microbial communities with geochemical processes in a freshwater lake. Surface sediment samples were collected from seven sites (i.e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 17 publications
0
6
1
1
Order By: Relevance
“…Compared with the regional background values of Poyang Lake [30], higher contents of four metals were revealed by this study. The content of Zn from all seven sites remarkably exceeded the background value, and Pb content from most sites also exceeded the background value except for sites NP and GJ.…”
Section: Resultscontrasting
confidence: 61%
“…Compared with the regional background values of Poyang Lake [30], higher contents of four metals were revealed by this study. The content of Zn from all seven sites remarkably exceeded the background value, and Pb content from most sites also exceeded the background value except for sites NP and GJ.…”
Section: Resultscontrasting
confidence: 61%
“…Thus far, A growing body of studies suggested that pH [13,30], organic matter [31], nitrogen [15], TOC [5], phosphorus [32] and heavy metal [33] were the critical drivers of microbial communities in lake sediments. However, the mentioned conclusions were drawn in terms of the comparing inter-lake, which have overlooked the significant effect of geographical distance.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the environmental factors contributing to the microbial assemblages in the lake sediments are essentially unclear, although previous studies have shown that pH [26,27], organic matter [28], nitrogen [29], phosphorus [30] and heavy metal [31] were the most important drivers of microbial communities in lake sediments. In this study, the results of RDA showed that TOC level mainly accounted for the changes of microbial community in Dianchi Lake sediment.…”
Section: Discussionmentioning
confidence: 99%